Virtualizing desktops & apps with Windows Server 2012 R2 inside out - Wright, Byron; Svidergol, Brian (Microsoft Press, 2015)
Conquer Windows Server 2012 R2 virtualization--from the inside out! Dive into Windows Server 2012 R2 virtualization--and really put your systems expertise to work. Focusing on both virtual desktop infrastructure and virtualized applications, this supremely organized reference packs hundreds of timesaving solutions, tips, and workarounds. Discover how the experts tackle Windows virtualization--and challenge yourself to new levels of mastery. Use virtualization to prevent business disruption, help improve security, simplify upgrades, and support mobile users Plan and deploy User State Virtualization for a consistent experience across locations and devices Define users, applications, and scenarios for any virtualization project Compare and deploy both session-based and virtual machine-based (VM-based) desktops Configure Client Hyper-V and work with VMs in a Client Hyper-V environment Install, design, configure, and administer Microsoft Application Virtualization (App-V) infrastructure and clients Sequence applications for efficient and reliable deployment Help secure remote access to virtual desktops with Remote Desktop Gateway (RD Gateway) Plan and implement pooled and personal desktops Monitor virtualized apps and desktops for health and performance.